2017
DOI: 10.1136/bcr-2017-219921
|View full text |Cite
|
Sign up to set email alerts
|

An unusual case of Cushing's syndrome due to bihormonal ACTH–prolactin secreting pituitary macroadenoma with rapid response to cabergoline

Abstract: A 23-year-old man presenting with florid Cushing's syndrome was found to have high plasma ACTH and very high serum prolactin. Pituitary MRI showed a large invasive macroadenoma. Low-dose cabergoline promptly suppressed both ACTH and prolactin levels within 2 weeks, with unexpected clinical and biochemical hypocortisolism requiring hydrocortisone replacement. Secondary hypogonadism was reversed. Clinical and biochemical remission of his Cushing's syndrome together with significant shrinkage of his macroadenoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…There are very few cases in the literature with a clinical phenotype of multiple pituitary hormone secretions 1 3–10. Our case has some important features, which need further elaboration.…”
Section: Discussionmentioning
confidence: 73%
“…There are very few cases in the literature with a clinical phenotype of multiple pituitary hormone secretions 1 3–10. Our case has some important features, which need further elaboration.…”
Section: Discussionmentioning
confidence: 73%
“…Dopamine receptor (DR) expression in ACTH-secreting PAs has been described [ 17 ]. While several case reports have demonstrated that ACTH-secreting PAs may respond to treatment with Cabergoline [ 18 , 19 , 20 , 21 , 22 , 23 ], the results in larger cohorts of patients bearing such tumors still remain controversial [ 24 , 25 ]. However, administration of dopamine agonists is worth considering as an option to treat these tumors [ 13 , 14 ], and a clinical trial on Cabergoline treatment in corticotroph PAs (Mumbai, India ( (accessed on 6 November 2021)) [ 26 ]; trial identifier: NCT00889525; Table 1 ) has been initiated.…”
Section: Emerging Targeted Treatment Strategies At the Molecular Levelmentioning
confidence: 99%
“…• PRL and LH; PRL and TSH [7] • GH and ACTH [9][10][11] • PRL and ACTH [5,7,12,13] • ACTH, LH, and TSH [7] • PRL, LH, FSH, and TSH [7] • GH, PRL, TSH, and a-SU [5] • GH, PRL, and ACTH [7,14] • GH, PRL, TSH, FSH, and aSU [15] Other less common combinations are also published [5]. Original examples of plurihormonal adenomas in the author series [7] are shown in…”
Section: Plurihormonal Pituitary Adenomasmentioning
confidence: 99%
“…Pituitary adenomas with the combination of different hormone groups from the same cell lineage (GH and prolactin or FSH and LH) are relatively common, but true plurihormonal adenomas with immunoreactivities that cross the cytogenetic lineage are rare in most series as "in Refs. [5,6,13]. "…”
Section: Pituitary Diseasesmentioning
confidence: 99%